Discipline-specific responses to a complex migraine case: a vignette-based survey among neurologists, psychiatrists, and family physicians - Karacı, Rahşan; Aydın Sünbül, Esra; Tekin, Nil; Taşdelen, Bahar; Arman, Ikbal Humay; Mayda Domaç, Füsun; Özge, Aynur (Frontiers in Neurology, 2025)
BackgroundChronic migraine (CM), especially when complicated by medication overuse headache (MOH), frequently coexists with psychiatric and somatic comorbidities that challenge conventional monodisciplinary management. Integrated, interdisciplinary care has been proposed as a solution, but real-world implementation remains limited.ObjectiveTo evaluate and compare the diagnostic reasoning, treatment preferences, and follow-up strategies among neurologists, psychiatrists, and family physicians when managing a complex case of CM with comorbidities and medication overuse.MethodsA case-based, multidisciplinary study was conducted using a structured vignette of a middle-aged woman with CM + MOH and multiple comorbidities. Ten questions were asked for each specialty (neurologists, psychiatrists, and family physicians) across Türkiye. Responses from 305 clinicians were analyzed via inductive thematic analysis and domain-specific agreement metrics.ResultsNeurologists prioritized headache semiology and pharmacological treatment; psychiatrists emphasized psychosocial burdens and behavioral interventions; and family physicians reported heterogeneous decision-making shaped by system-level constraints. Agreement levels varied by discipline and clinical domain. The level of awareness of multimorbidity was high, yet interdisciplinary coordination was limited. Across groups, common barriers included stigma, poor treatment adherence, and unclear referral pathways.ConclusionCM + MOH patients with multimorbidity constitute a clinically complex population requiring interdisciplinary collaboration. The differences in approach highlight the need for structured care pathways and shared decision-making frameworks. Family physicians can act as pivotal coordinators if supported by headache-specific training and referral networks.